Sinonasal Hyalinizing Adenoid Cystic Carcinoma Is Molecularly Different from Its Salivary and Breast Counterparts - Ebtissam Alerraqi; Essam Mandour; Mariz Faltas (MDPI AG, 2023)
Adenoid cystic carcinoma (AdCC) is known to behave differently based on its location, histologic features, and molecular profile. Despite this understanding, efforts to use these molecular findings to develop personalized treatments have not yet been successful. The purpose of this retrospective study is to examine the molecular characteristics of AdCC with various histologic features in three different locations. A reference group of 20 classic cribriform AdCC cases from the parotid gland was included, along with 10 salivary AdCCs (Group 1), 10 sinonasal AdCCs with hyalinization (Group 2), and 10 solid mammary AdCCs with basaloid features (Group 3). Tissue samples were processed and tested using various molecular techniques, and the Wilcoxon signed-rank test was used to compare the different groups. Molecular data were obtained for both common and rare cases of sinonasal, salivary, and mammary AdCCs, revealing differences in molecular features depending on the tumor's location. The molecular profile of the AdCCs in the experimental group varied depending on the site, with MYB gene rearrangements being common in all cases. We report the first MYB::KMT2C/D fusions in a subset of salivary AdCCs and sinonasal AdCCs but not in mammary adenoid cystic carcinoma with basaloid features. We conclude that co-occurring genetic alterations may vary among different sites and may have implications for the prognosis and treatment plan of AdCC. More research is needed to fully understand the mechanisms of KMT2C and KMT2D mutations in the development and progression of head and neck cancer, including their interactions with the NOTCH pathway.